2017
DOI: 10.1177/1010428317695962
|View full text |Cite
|
Sign up to set email alerts
|

Specific tumor-derived CCL2 mediated by pyruvate kinase M2 in colorectal cancer cells contributes to macrophage recruitment in tumor microenvironment

Abstract: Development of colorectal cancer has been considered as a result of imbalance of pro-and anti-inflammatory intestinal microenvironment accompanied by macrophage recruitment. Despite macrophages are implicated in remodeling tumor microenvironment, the mechanism of macrophage recruitment is not fully elucidated yet. In this study, we reported clinical association of highly expressed pyruvate kinase M2 in colorectal cancer with macrophage attraction. The conditioned medium from Caco-2 and HT-29 cells with deplete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Immunohistochemistry and immunofluorescence were performed as described in our previous work. 26,27 The sections were deparaffinized, rehydrated, blocked with goat serum and incubated with…”
Section: Immunohistochemistry (Ihc) and Immunofluorescence(if)mentioning
confidence: 99%
“…Immunohistochemistry and immunofluorescence were performed as described in our previous work. 26,27 The sections were deparaffinized, rehydrated, blocked with goat serum and incubated with…”
Section: Immunohistochemistry (Ihc) and Immunofluorescence(if)mentioning
confidence: 99%
“…It is reported that p53 can inhibit Bcl-2, while it also activates Bax and Bak proteins. Bax protein tends to activate the death effect factor caspase or change the cell membrane permeability, 51 resulting in the release of small molecules and ions, by cytochrome C, through the cell membrane, therefore promoting the apoptosis of the cell. When Bcl-2 is dominant, then the change in Bcl-2/Bax can regulate apoptosis, and cell possesses antiapoptotic effects.…”
Section: ■ Discussionmentioning
confidence: 99%
“…What’s more, REC8 interacted with NF-κB, leading to inhibit NF-κB activity. Dynamic change NF-κB p65 activity is critical event in nucleus shuttle [ 32 ]. Depletion of REC8 expression in BGC823 cells drastically contributed the binding of NF-κB to VEGF promoter, leading VEGF transcription.…”
Section: Discussionmentioning
confidence: 99%